The wisdom of plagues : lessons from 25 years of covering pandemics - McNeil, Donald G., Jr (Simon & Schuster, 2024)
"For millions of American's, Donald McNeil was a comforting voice when the Covid-19 pandemic broke out. He was a regular reporter on the New York Times's popular podcast The Daily and told listeners early on to prepare for the worst. Over the years, he'd covered AIDS, Ebola, influenza, malaria, MERS, SARS, tuberculosis, and Zika, and he quickly realized that an obscure virus in Wuhan, China, was destined to grow into a global pandemic rivaling the 1918 Spanish flu. Many science reporters understand the basics of diseases--the way a virus mutates, for example, or what goes into making a vaccine. But few understand the psychology of how small outbreaks turn into pandemics, why people refuse to believe they're at risk, or why they reject protective measures like quarantine or vaccines. By the time McNeil wrote his last New York Times stories, he had not lost his compassion--but he had grown far more stonehearted about how governments should react. While every epidemic is different, failure is the one constant. In The Wisdom of Plagues, McNeil offers tough, prescriptive advice on what can be better prepared for the inevitable next pandemic"--Dust jacket flap.